Long‐term outcomes of lung transplant recipients with hepatitis C infection: a retrospective study of the U.S. transplant registry. Issue 3 (9th June 2016) - Koenig, A.; Stepanova, M.; Saab, S.; Ahmed, A.; Wong, R.; Younossi, Z. M.
Summary: Background: Chronic hepatitis C patients in need of a lung transplant are often considered ineligible due to their infection. Aim: To assess the association of hepatitis C virus (HCV) infection with long‐term outcomes of lung transplants. Methods: From the Scientific Registry of Transplant Recipients (1995–2011), we selected all adults with and without HCV infection who underwent lung transplantation. Results: A total of 17 762 lung transplant recipients were included (55.5% bilateral). Of those, 319 (1.83%) had positive HCV serology. The HCV‐positive recipients were 1.6 years younger, less Caucasian and more African‐American, and had a significantly higher rate of co‐infection with hepatitis B virus (all P < 0.001). Post‐transplant patients were discharged alive at similar rates regardless of HCV status: 88.4% in HCV+ vs. 90.3% in HCV− ( P = 0.25). The mortality rates were also similar at 1 and 2 years after transplantation (20.7% in HCV+ vs. 19.2% in HCV− and 31.6% in HCV+ vs. 28.9% in HCV−, respectively; both P > 0.05), but at post‐transplant year 3 year, mortality rate in HCV+ became significantly higher (42.5% vs. 36.4%, P = 0.04) and remained higher for the duration of the follow‐up (mean 9.1 years, max 18.4 years). In multivariate survival analysis, after adjustment for confounders, being HCV+ was associated with higher mortality: adjusted hazard ratio 1.24 (1.04–1.46), P = 0.01. No association of HCV infection with time to graft loss was found ( P = 0.92). Conclusions: Chronic HCV infection is associated with a moderate increase in post‐lung transplant mortality. Treatment of HCV in lung transplant recipients may, therefore, result in improvement of post‐transplant outcomes.